Trade Liberalization, Consumption, and Real Exchange Rate in Seven ASEAN+6 Countries - Setiawan, Sigit (Journal of Economics and Behavioral Studies, 2017)
Trade liberalization has been mushrooming in the globalization era. The trade liberalization policy adoption by one country will be followed shortly by another. Although trade liberalization policy is strongly advocated by international organizations, a few prominent economists argue there is no ‘one fits for all’ policy. Thus, the policy effect altogether with other relevant aspects still needs to be explored in case by case basis, including ASEAN+6 regions. This paper is intended to analyze the relationship of trade liberalization and consumption on the real exchange rate in seven ASEAN+6 countries – the most dynamic region during period 2000 – 2011, a period covering subprime mortgage crisis. With data panel approach, the paper investigates the relationship of trade liberalization and consumption on real exchange rate while taking into account level of country’s income and crisis effect. The resulted model finds significant relationship in the overall and individual effect of tariff and terms of trade change as proxies of trade liberalization, consumption, level of country’s income, and subprime mortgage crisis on real exchange rate.